The importance of distance delimitation impulse in the technical learning of hurdle technique (2016)
The aims of this work are: - To verify scientifically that the location of visual limiting references of the impulse, when in the correct place, redirects the action of the athletes who are new to jumping hurdles, helping them to improve their performance. - To facilitate beginners to progress to, with guarantees of technical success, the official heights of the hurdles and the distances between them.